2017
DOI: 10.1039/c6qo00756b
|View full text |Cite
|
Sign up to set email alerts
|

KI-mediated radical multi-functionalization of vinyl azides: a one-pot and efficient approach to β-keto sulfones and α-halo-β-keto sulfones

Abstract: Transition metal-free oxidative coupling of vinyl azides with sulfonyl hydrazines is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 48 publications
0
38
0
1
Order By: Relevance
“…Yu and co‐workers utilized vinyl azides as starting materials in the construction of β ‐keto sulfones (Eq. 21‐1).…”
Section: Sulfonyl Radiacls‐mediated Reactionsmentioning
confidence: 99%
“…Yu and co‐workers utilized vinyl azides as starting materials in the construction of β ‐keto sulfones (Eq. 21‐1).…”
Section: Sulfonyl Radiacls‐mediated Reactionsmentioning
confidence: 99%
“…One year later in 2017, Yu et al [88] reported a transition metal-free, reagent-controlled oxosulfonylation reaction between vinyl azides and sulfonyl hydrazines. According to this radical process, a mixture vinyl azides 35a, sulfonyl hydrazines 35b in DMSO was kept on stirring in presence of KI as an additive and TBHP as a radical initiator at 25°C to achieve β-keto sulfones 35c in 70-90% yields (Scheme 35).…”
Section: In Alkene Systemmentioning
confidence: 99%
“…78 In a similar vein, sulfonyl hydrazines have been shown to be a valuable source of sulfonyl radicals in the KI/tert-butyl hydroperoxide-mediated oxidative coupling with vinyl azides (Scheme 34). 79 Further reaction of the resulting βketo sulfones 141 with the corresponding potassium halide under acidic conditions affords α-halo-β-keto sulfones 142, through putative intermediates 143. Very recently, a convenient and functional-group tolerant silver(I)-catalyzed aminosulfonylation reaction has been developed by our group, using readily available terminal alkynes, TMSN 3 as an ammonia source, and sodium sulfinates as a sulfonyl source (Scheme 35a reaction proceeds through a sequence of silver-catalyzed alkyne hydroazidation, followed by attack of the sulfonyl radical onto the in situ generated vinyl azide.…”
Section: Reduction Of 131 By Mes-acrmentioning
confidence: 99%